CSR dan Nilai Perusahaan: Peran Strategis Karakteristik Dewan dalam Perbankan Konvensional BEI - Riva Rivelyanti Simanullang; Riyan Harbi Valdiansyah (Politeknik Ganesha Medan, 2025)
This study aims to examine the effect of Corporate Social Responsibility (CSR) disclosure on firm value, considering the moderating roles of board size and board independence. The research covers all non-sharia banks listed on the Indonesia Stock Exchange (IDX) during 2022–2024. Using purposive sampling, 42 companies were selected, yielding 126 firm-year observations. Data analysis employed Moderated Regression Analysis (MRA) with EViews 13. The results reveal that CSR disclosure has a negative and significant effect on firm value (coefficient = -4.796; p = 0.0438). Board size moderates this relationship positively, mitigating the negative impact of CSR on firm value, although the effect is only marginally significant at the 10% level (interaction coefficient = 1.272; p = 0.0539). In contrast, board independence does not show a significant moderating effect (p = 0.1539). These findings suggest that while the market still perceives CSR costs as financial burdens, governance mechanisms—particularly board size—shape how CSR translates into firm value. Theoretically, the study supports stakeholder theory and legitimacy theory, which emphasize the importance of governance-based CSR management. Practically, banking institutions are advised to strengthen the role of boards in designing CSR strategies that are more strategic, directed, and credible to generate sustainable value.